Efficacy and safety of a herbal mixture (Viron® tablets) in the treatment of patients with chronic hepatitis C virus infection: a prospective, randomized, open-label, proof-of-concept study - Shawkat H; Yakoot M; Shawkat T; Helmy S (Dove Medical Press, 2015)
Hisham Shawkat,1 Mostafa Yakoot,2 Tarek Shawkat,1,3 Sherine Helmy4 1KEMET Clinic, Cairo, Egypt; 2Green Clinic and Research Center, Alexandria, Egypt; 3Internal Medicine Department, Cape Canaveral Hospital, Cocoa Beach, FL, USA; 4Pharco Corporation, Alexandria, Egypt Background: Development of an optimal interferon-free regimen for chronic hepatitis C virus infection is believed to require the combination of different drug classes to provide good antiviral efficacy, clinical and quality of life benefits, as well as a high barrier to resistance. Viron® is a new herbal drug in film-coated tablet form, and is based on a mixture of herbs with known hepatoprotective and antiviral properties. We conducted this study to explore the safety and the potential clinical and quality of life benefits of this product in patients with chronic hepatitis C infection.Methods: Eighty-two consecutive patients presenting to our outpatient clinics as already-known or newly-diagnosed cases of chronic hepatitis C virus (HCV) infection, were entered into the study and randomized to three groups to receive escalating doses of Viron for 6 months. Virological, clinical, and enzyme responses, as well as quality of life index scores for chronic liver disease were compared between the groups.Results: Of the 20 patients treated with the highest dose of Viron (three tablets twice daily), two (10%) had a complete virological response at the end of treatment (ETR) and two (10%) had a partial ETR, defined as a decrease in viral load of at least 2-log10 at the end of 6 months of treatment, whereas patients treated with the medium dose (two tablets twice daily) and the lowest dose (one tablet twice daily) showed a significantly lower ETR (P=0.043). Alanine aminotransferase levels and scores on the Chronic Liver Disease Questionnaire improved to a significantly greater extent in the highest dose group (P=0.007 and P=0.021, respectively). No serious adverse effects attributable to the herbal formulation were reported in any of the groups, apart from mild transient nausea, bloating, giddiness, and headache in two patients in the group receiving two tablets twice daily and in three patients in the group receiving three tablets twice daily.Conclusion: We conclude that this herbal formulation is potentially safe and may offer some added clinical and quality of life benefits when used in the treatment of patients with chronic hepatitis C virus infection. Larger studies could be warranted to evaluate the effects of using this formulation as an add-on therapy to an all-oral combination of a directly acting antiviral drug protocol in the treatment of chronic hepatitis C. Keywords: chronic hepatitis C virus, proof-of-concept study, safety, efficacy